Mechanisms of implicit learning : connectionist models of sequence processing - Cleermans, Axel (Neural network modeling and connectionism, 1993)
Implicit learning: Explorations in basic cognition The SRN model: Computational aspects of sequence processing Learning a finite-state grammar Discovering and using path information Encoding nonlocal context Sequence learning as a paradigm for studying implicit learning Learning the structure of event sequences Sequence learning: Further explorations Sequence learning and memory disorders Attention and sequence structure Elementary sequence learning and the effects of explicit knowledge Encoding remote context Long-distance contingencies and prediction-based learning Comparison with other architectures for sequence processing Explicit sequence learning An explicit prediction task Transfer to new material General discussion Prediction-relevance and context representation Attention, awareness, and the role of explicit knowledge Conscious and unconscious knowledge Transfer and abstraction